(x-6)(x-3)=-1

Simple and best practice solution for (x-6)(x-3)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)(x-3)=-1 equation:



(x-6)(x-3)=-1
We move all terms to the left:
(x-6)(x-3)-(-1)=0
We add all the numbers together, and all the variables
(x-6)(x-3)+1=0
We multiply parentheses ..
(+x^2-3x-6x+18)+1=0
We get rid of parentheses
x^2-3x-6x+18+1=0
We add all the numbers together, and all the variables
x^2-9x+19=0
a = 1; b = -9; c = +19;
Δ = b2-4ac
Δ = -92-4·1·19
Δ = 5
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-\sqrt{5}}{2*1}=\frac{9-\sqrt{5}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+\sqrt{5}}{2*1}=\frac{9+\sqrt{5}}{2} $

See similar equations:

| 16x+5=12x-7 | | 5(y-3)=-25 | | p/15=29 | | (2-9y)(17-4y)=4/5 | | X²-4x-4=0 | | 72=u+3 | | 5+3(x+1)=8 | | 2x(+5)=16 | | 11i+7=40 | | 7i+7=40 | | (5y÷)+2(2y-6)y=9 | | 19000=125t-122 | | (30+-1y)+y=30 | | 106÷4z–6= | | 49^(5x+2)=((1)/(7))^(11-x) | | (30-y)+y=30 | | 4^x=−70 | | 3x^2=3888 | | a(7.5)=60 | | 0.6x=125 | | 9x-13=11x-27 | | y=-4+210 | | 32-m=18 | | 4y–3=11 | | 44n+6=2n−4| | | (b+8)(5b-4)=0 | | 2/7=3.5/x | | y-4y+4y=0;y(0)=12;y(0)=-3 | | 24=z/0.3 | | 7x2-6=8x | | 5x–1=2x+8 | | 5/7p+3/4p=82 |

Equations solver categories